IL-6 and IL-27 play both distinct and redundant roles in regulating CD4 T-cell responses during chronic viral infection - Harker, James A.; Greene, Trever T.; Barnett, Burton E.; Bao, Phuc; Dolgoter, Aleksandr; Zuniga, Elina I. (Frontiers in Immunology, 2023)
The IL-6 cytokine family signal through the common signal transduction molecule gp130 combined with a cytokine specific receptor. Gp130 signaling on CD4 T cells is vital in controlling chronic infection of mice with lymphocytic choriomeningitis virus clone 13 (LCMV Cl13) but the precise role of individual members of the IL-6 cytokine family is not fully understood. Transcriptional analysis highlighted the importance of gp130 signaling in promoting key processes in CD4 T cells after LCMV Cl13 infection, particularly genes associated with T follicular helper (Tfh) cell differentiation and IL-21 production. Further, Il27r-/-Il6ra-/- mice failed to generate antibody or CD8 T cell immunity and to control LCMV Cl13. Transcriptomics and phenotypic analysis of Il27r-/-Il6ra-/- Tfh cells revealed that IL-6R and IL-27R signaling was required to activate key pathways within CD4 T cells. IL-6 and IL-27 signaling having distinct and overlapping roles, with IL-6 regulating Tfh differentiation, IL-27 regulating CD4 T cell survival and both redundantly promoting IL-21.